A body-centered cubic Zr50Ti35Nb15 medium-entropy alloy with unique properties. (15th March 2020) - Yan, Xuehui; Zhang, Yong
Abstract: The center of phase diagram, relatively high-disordered region, often has few alloy systems available, especially for traditional ternary alloy systems. Here, we develop a novel Zr50 Ti35 Nb15 alloy near the center of phase diagram, as a body-centered cubic (bcc) solid solution phase, which displays a unique combination of Young's modulus of 62 GPa, yield strength of 657 MPa, tensile ductility of 21.9%, and excellent corrosion resistance ( Ecorr =422 mV, Ipit =0.336 µA/cm 2 ). The excellent mechanical properties of this alloy are related to dislocation slip and deformation twins. This result also proves that the disordered structure is valuable for traditional alloy systems. Graphical abstract: Image, graphical abstract